PERANCANGAN POSITIONER UNIT PADA AUTOMATION FORGING LINE MENGGUNAKAN METODE DIETER DAN TRIZ EFFECT DATABASE - Sudarmaji, Heri; Pelani, Akhmad (Technologic, 2018)
The aim of designing the positioner unit is to get the machine design which appropiate to the customer design requirements. The process of machine design carried out by the dieter method, which is follow theese steps: 1. define the problem, 2. gathering information, 3. conceptual design, 4. embodiment design, and 5. detail design. The positioner unit has three functions: reduce billet speed, positioning billet to be easily taken by the robot gripper, and inspect the billet based on temperature. Reduce billet speed function using the pendulum concept, positioning billet function using the concept of v block jig which can be rotated by the hinge system with a pneumatic cylinder as the actuator, and for the billet temperature inspection function using a temperature sensor. To find solution for sub functions, Dieter Metode was combined by TRIZ Methode, especially TRIZ effect database to find solution alternative possibilities. By using these concepts, the positioner unit which appropiate with the customer requirements can be obtained.